2006
DOI: 10.1103/physrevlett.96.137401
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Light Emission of Two Lateral Tunnel-Coupled(In,Ga)As/GaAsQuantum Dots Controlled by a Tunable Static Electric Field

Abstract: Lateral quantum coupling between two self-assembled (In,Ga)As quantum dots has been observed. Photon statistics measurements between the various excitonic and biexcitonic transitions of these lateral quantum dot molecules display strong antibunching confirming the presence of coupling. Furthermore, we observe an anomalous exciton Stark shift with respect to static electric field. A simple model indicates that the lateral coupling is due to electron tunneling between the dots when the ground states are in reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(133 citation statements)
references
References 26 publications
3
130
0
Order By: Relevance
“…First, the QDM considered here can be obtained by a unique combination of molecule beam epitaxy and in situ atomic layer precise etching [67,68]. Secondly, the strong coupling between quantum dot and cavity modes has been realized in the previous studies [69][70][71], which improves the experimental feasibility of our schemes.…”
Section: Effects Of Qdm's Spontaneous Decay and Photon Leakagementioning
confidence: 71%
“…First, the QDM considered here can be obtained by a unique combination of molecule beam epitaxy and in situ atomic layer precise etching [67,68]. Secondly, the strong coupling between quantum dot and cavity modes has been realized in the previous studies [69][70][71], which improves the experimental feasibility of our schemes.…”
Section: Effects Of Qdm's Spontaneous Decay and Photon Leakagementioning
confidence: 71%
“…Previous experiments on planar QDCs have focused on either growth and structural characterizations or spectroscopy of QD pairs. [10][11][12][13]17,18 Spectroscopic studies conducted on individual QDCs with more than two QDs have not been previously reported. Such studies are instrumental in addressing key challenges in controlling the properties of QDCs and evaluating their potential for scalability.…”
mentioning
confidence: 99%
“…17 Both of these papers predicted sensible signatures of tunnel coupling in charged states. However, the experimental evidence of controllable interdot tunnel coupling in LQDMs [18][19][20][21] remains indirect. The center-to-center distance between a QD pair in a LQDM is about ten times larger than the separation in a VQDM; the tunneling strength is expected to be significantly weaker.…”
Section: Introductionmentioning
confidence: 99%